Model-based acoustic rendering based on plane wave decomposition. (March 2016) - Bianchi, Lucio; Antonacci, Fabio; Sarti, Augusto; Tubaro, Stefano
Abstract: In this manuscript we propose an analytic solution to the problem of sound field rendering, based on the plane wave decomposition, which is here derived with reference to the Herglotz density function. The plane wave decomposition encodes the directional contributions to the sound field, and allows us to describe elementary sound fields in a model-based fashion, parameterized only by the source location. We show how this representation can be exploited for rendering purposes using a wide variety of loudspeaker arrangements. We start by deriving closed-form expressions for the loudspeaker weights based on the plane wave decomposition and we validate this derivation with an analysis of the reproduction error for the case of a circular array of speakers. We then show how to extend the proposed method to non-circular geometries. We assess the performance of the proposed rendering solution for various array configurations, offering a comparison with state-of-the-art analytical rendering techniques.